The 3' terminal sequences of human alpha and beta globin messenger RNAs: comparison with rabbit globin messenger RNA. - Proudfoot, N; Longley, J (1976)
Sequences of 43 and 70 nucleotides adjacent to the 3' terminal poly(A) of human alpha and beta globin mRNAs have been established. Sequence analysis of complementary DNA from both normal and thalassemic globin mRNA preparations was carried out using endonuclease IV digestion and limited synthesis procedures. The two RNA sequences are 83% homologous to rabbit globin mRNA (Proudfoot, 1976), and a part of the alpha globin mRNA sequence codes for the carboxy terminus of human alpha globin Constant Spring (Clegg, Weatherall, and Milner, 1971). This latter result predicts that the 3' noncoding region of human alpha globin mRNA is exactly 112 nucleotides, while the 5' noncoding region is probably about 50 nucleotides.